O.I. Glazova and Her Contribution to the Development of Domestic Emergency Clinical Toxicology - Y. S. Goldfarb; S. A. Kabanova; M. M. Potskhveriya; V. I. Sleptsov (Неотложная медицинская помощь)
The biography of Olga Ivanovna Glazova, doctor of medical sciences, honored doctor of the RSFSR, member of the Scientific Council of the N.V. Sklifosovsky Research Institute, is an example of an exceptionally successful diversification of scientific activity, both in the field of cardiology and clinical toxicology, which is the new direction of Russian medicine.There are suggestions in the works of O.I. Glazova similar to modern ideas of acute poisonings (AP), as confirmed by later publications in this field. The pathogenetic approach to the study of AP was considered by O.I. Glazova from the perspective of the teachings of I.P. Pavlov about the body as a single entity, and the action of the poison hypothetically dependent on its concentration in the blood. She emphasized the need for the early removal of poison from the body to prevent the adverse course of poisoning. The role of antidote therapy as an example of a detoxification approach to the treatment of AP was noted, while antidotes for parenteral administration were recommended in order to increase the effectiveness of detoxification.Some thoughts were expressed about the dependence of the toxic effects of poisons on physical and chemical properties, as well as similar ideas about the quantitative measure of poisoning, selective and situational toxicity, the presence of concentration, space and temporal factors in the pathogenesis of poisoning. The systematization of the AP was presented.Thus, O.I. Glazova made a significant contribution to the study of AP thanks to her enthusiasm, constant creative eagerness and high professional competence, which contributed to a significant growth the role of representatives of the emergency medical clinic in AP treatment, and in turn positively affected the regularity and quality of further research in this area.Authors declare lack of the conflicts of interests.